Haricot vegetation under the influence of foreign intolution seeds and approvals - Новицька, Н. В.; Мартинов, О. М.; Доктор, Н. М. (Scientific Progress & Innovations, 2018)
The article is devoted to the results of the study of the duration of the vegetation period of the beans and its individual phases for mid-late varieties of Mavka, Pearl, Nadiya depending on the level of fertilization and inoculation of seeds by «Risobofit P» in the conditions of Transcarpathia of Ukraine. Field experiments were laid on the collector-demonstration field at the NUPiP of Ukraine «Mukachevo Agrarian College» in the Transcarpathian region on turf-podzolic heavy-soil soils. Mineral fertilizers were introduced in the form of ammonium nitrate (34.4 % N), phosphorous flour (30 % P), kalimagnesia (26–28 % K, 11–18 % Mg); additionally carried out liming of soils at the rate of 3 t/ha. The inoculation of seed beans was carried out on the day of sowing by «Risobofit» (mark P), which contains the symbiotic nitrogen fixing bacteria of the genus Rhizobium phaseoli from the Institute of Agroecology and Nature Management of NAAS. It has been established that in the conditions of Transcarpathia, the vegetation of mid-season varieties of beans varies from 93 to 113 days depending on variety characteristics, fertilization and inoculation of seeds. Hope grade reached earlier than others and the period of vegetation it was 8–10 days shorter. Application of seed inoculation prolonged the period of vegetation of beans varieties compared to variants without seed inoculation on a different background of fertilizer for 3–5 days. The increase in nitrogen fertilizers up to 60 kg/ha prolonged the vegetation of the studied bean varieties for 8–13 days. For the application of nitrogen fertilizers in the normal range from 45 to 60 kg/ha against the background of PK, the vegetation period was the same, both in the variants with and without inoculation. The introduction of nitrogen fertilizers in the normal range from 45 to 60 kg/ha on the background of PK resulted in inhibition of the nitrogenase activity of the tubers on the roots of the studied soybean varieties and the plant nutrition was carried out solely at the expense of mineral fertilizer forms.